Tea on the terrace : hotels and Egyptologists' social networks, 1885-1925 - Sheppard, Kathleen L. (Manchester scholarship online, 2023)
A history of travel, tourism, and Egyptology, 'Tea on the Terrace' examines what Egyptologists did between home and the field site and how their activities in hotels and on dahabeahs impacted the development of the discipline at the turn of the 20th century